Observation of gamma(1S) pair production in proton-proton collisions at root s=8 TeV - (:unkn) unknown (SPRINGER, 2017)
Pair production of gamma(1S) mesons is observed at the LHC in proton-proton collisions at root s = 8 TeV by the CMS experiment in a data sample corresponding to an integrated luminosity of 20.7 fb(-1). Both gamma(1S) candidates are fully reconstructed via their decays to mu(+) mu(-). The fiducial acceptance region is defined by an absolute gamma(1S) rapidity smaller than 2.0. The fiducial cross section for the production of gamma(1S) pairs, assuming that both mesons decay isotropically, is measured to be 68.8 +/- 12.7 (stat) +/- 7.4 (syst) +/- 2.8 (B) pb, where the third uncertainty comes from the uncertainty in the branching fraction of gamma(1S) decays to mu(+) mu(-). Assuming instead that the gamma(1S) mesons are produced with different polarizations leads to variations in the measured cross section in the range from 38% to +36%.
Keywords: Hadron-Hadron scattering (experiments); Quarkonium; DOUBLE PARTON SCATTERINGS; HADRONIC PRODUCTION; COHERENCE; J/PSI